Nanoparticles Suspensions as Optical Power Limiting Synthsization and Characterization - Gofran Hadi (Journal of Global Pharma Technology, 2020)
In this study, the investigation of the nonlinear and optical properties of nanoparticles (AgNPs) in distilled water with gold nanoparticles (AuNps) was investigated. The non-linear absorption coefficient of nanotubes was measured by Z-scan. Nanonuclear AuNps with AgNPs under exposure to nano-laser pulses at 532 nm as well as 405 nm and 650 nm. The results showed that nonlinear diffusion can increase the performance of the optical marker. A theoretical analysis is proposed Investigate non-linear behavior observed from AgNPs with AuNPs. Shows that the dispersion of non-linear light occurs at high intensity because of the inverse refractive mismatch between silver nanoparticles with gold and water. TheZ- scan experimental data were provided with the proposed theoretical model, allowing the extraction of nonlinear absorption coefficients and linear and nonlinear propagation coefficients for AgNP suspension with AuNPs.